Journal of Compassionate Health Care - Shea, Sue; Lionis, Christos
Journal of Compassionate Health Care provides a vehicle for bringing together multidisciplinary perspectives, research and initiatives concerning the topical concept of compassionate care. The journal invites international contributions and promotes research, discussion and the sharing of experiences with the ultimate goal to improve clinical effectiveness and quality of health care. Journal of Compassionate Health Care links medicine and social science in a multidisciplinary journal, thus bringing a number of concepts and approaches together within the field of compassionate care. The journal welcomes manuscripts in relation to: Theoretical and therapeutic approaches Neurobiological approaches Implementation and evidence based provision of compassion Development of tools for measuring compassion Assessment of the effectiveness of compassionate care interventions Organisational/structural/managerial issues Compassion fatigue and burnout Philosophical and ethical considerations Methods for teaching and sustaining compassion.